Exercício de linguagem: o ethos discursivo e a competência discursiva em questões de Língua Portuguesa do ENEM 1998 e 2016 - Rocha, Beatriz Silva [UNIFESP] (2019)
The National High School Examination (ENEM) was created in 1998 and is currently one of the main instruments for the evaluation of Brazilian high school and the selection of candidates for higher education, especially in federal universities, through the Unified Selection System (SISU). Its results are considered as a strategic measure for the promotion and improvement of the quality of education in the country. The exam, consisting of multiple choice questions, evaluates the student's ability to deal with problem situations using different skills and abilities in decision-making. Considering the expanded reach that the test has conquered over the years, this qualitative research examined 5 questions from the Portuguese Language area of the 1998 edition and 5 questions from the 2016 edition of the Language, Codes and Their Technologies of ENEM, from the theoretical-methodological perspective of the French Discourse Analysis, specifically the studies of Dominique Maingueneau (1997, 2004a, 2008a, 2008b, 2012, 2015). It was verified that in the group of the 10 questions of Portuguese Language what discursive competences were required, according to Maingueneau's theory (2004) and analyzed the discursive ethos of the enunciator of the questions. In addition to the discursive ethos and discursive competence, observing the concern of official exam documents with the interdisciplinarity, the objective was to investigate whether, on the same questions, there was an interdisciplinary work. For such investigation, the research anchored in the considerations of Ivani Fazenda (1979/2002). The methodology included the analysis of two official documents, Portaria MEC n° 438, de 28 de Maio de 1998, which establishes the exam in 1998, and Edital n° 10, de 14 de Abril de 2016, which focused on the 2016 edition in order to investigate how ENEM was specifically configured in the 1998 and 2016 editions and whether the questions actually met the specified skills and abilities. The analysis evidenced that the official documents were built under the interdisciplinary precept and privileged the evaluation of different languages. It was verified that the questions of both editions presented interdisciplinarity, and the need of interaction of the discursive competences for the understanding of the base text. In the 1998 edition, a discursive ethos of a less fixed enunciator in relation to 2016 was constituted, marked by the construction of a "teach image" or didactic scenography in the questions. The discursive ethos of the 2016 questions demonstrated a deletion of the enunciator, in favor of an objective and technical tone.